Supply Chain Optimization: Current Practices and Overview of Emerging Research Opportunities - Hassini, Elkafi (INFOR. Information systems and operational research, 2008)
The purpose of this editorial is to introduce a special issue "Optimization and Simulation Models in Supply Chain Management" that looks at optimization and simulation applications in supply chain management. In addition to introducing the papers in this issue and summarizing their major contributions, we give a brief overview of the current practice in supply chain optimization and the prospects for future research in this field.